The Influence of Quality of Work Life (QWL), Organizational Commitment (OC) and Transformational Leadership on Organizational Citizenship Behavior (OCB) - Nelis Fadhila Rimatanti; Akhmad Darmawan (Universitas Muhammadiyah Purwokerto, 2023)
This study aims to identify and analyze the effect of quality of work life (QWL), organizational commitment (OC) and transformational leadership on organizational citizenship behavior at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. Sampling using purposive sampling method through a questionnaire. The sample used was 165 nurses. The analysis technique used in this study uses the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that quality of work life has a positive and significant effect on organizational citizenship behavior, organizational commitment has a positive and insignificant effect on organizational citizenship behavior, and transformational leadership has a positive and significant effect on organizational citizenship behavior. Based on the test results of the R² adjusted coefficient of determination of 18.9%.